The SEIRS Model Simulation of Cholera Transmission with Treatment and Vaccination - Nur Elini Jauhari, (Applied Mathematics and Computational Intelligence (AMCI), 2022)
Cholera is an acute diarrhoea infection caused by the bacterium ‘Vibrio cholerae’ ingestion of contaminated food or water. Cholera remains a global public health threat as well as an indicator of inequity and a lack of social development. This research aims to investigate the impact of treatment and vaccination on cholera disease transmission using the SEIRS model. In this research, the dynamic behaviour of susceptible, exposed, infected, and recovered populations are illustrated using three different simulation cases: the influence of treatment only, the influence of vaccination only, and the influence of a combination of treatment and vaccination on the SEIRS model, respectively. Additionally, this research also analyses the effects of treatment factors and vaccination variation on the infected populations. The basic reproductive number is also calculated with respect to the variation in vaccination rate. To illustrate the theoretical results, some numerical simulations are provided. The findings indicate that adequate vaccination and treatment levels are required to eradicate cholera from the population.